SOCS Proteins Participate in the Regulation of Innate Immune Response Caused by Viruses - Huang, Shanzhi; Liu, Ke; Cheng, Anchun; Wang, Mingshu; Cui, Min; Huang, Juan; Zhu, Dekang; Chen, Shun; Liu, Mafeng; Zhao, Xinxin; Wu, Yin; Yang, Qiao; et al. (Frontiers in Immunology, 2020)
The host immune system has multiple innate immune receptors that can identify, distinguish, and react to viral infections. In innate immune response, the host recognizes pathogen-associated molecular patterns (PAMP) in nucleic acids or viral proteins through pathogen recognition receptors (PRRs), especially toll-like receptors (TLRs), and induces immune cells or infected cells to produce type I Interferons and pro-inflammatory cytokines, thus when the virus invades the host, innate immunity is the earliest immune mechanism. Besides, cytokine-mediated cell communication is necessary for the proper regulation of immune responses. Therefore, the appropriate activation of innate immunity is necessary for the normal life activities of cells. The suppressor of the cytokine signaling proteins (SOCS) family is one of the main regulators of the innate immune response induced by microbial pathogens. They mainly participate in the negative feedback regulation of cytokine signal transduction through Janus kinase signal transducer and transcriptional activator (JAK/STAT) and other signal pathways. Taken together, this paper reviews the SOCS proteins structures and the function of each domain, as well as the latest knowledge of the role of SOCS proteins in innate immune processes caused by viral infections and the mechanisms by which SOCS proteins assist viruses to escape host innate immunity. Finally, we discuss potential values of these proteins in future targeted therapies.